Police culture, discourse, and the construction of Canadian police officers’ identity - Joe Luis Couto (Journal of Community Safety and Well-Being)
Canadian police officers work within a deeply rooted and unique police culture that remains anchored to traditional occupational norms and values often resistant to change. Yet, policing is under pressure from elected officials and the public to meet changing social realities and public expectations. Inevitably, officers experience an identity crisis when they feel the strong and persistent pull of their tradition-bound culture while their services attempt to be more inclusive and progressive. Utilizing critical discourse analysis (CDA) and specifically Fairclough’s dialectical-relations approach, this study explores how identity is constructed and reinforced through discourse within and by police culture to create the idea of what it means to be a cop. Using data from an analysis of semi-structured interviews with 30 currently serving police officers in four Canadian police services, it considers how the language of policing (verbal, written, visual) is used to construct police identity. The data show that through the use of police-specific discourse prior to, during, and after recruitment, police culture retains an all-powerful hold on officers’ identity construction before and during recruitment and throughout their careers. It also represents a barrier to more equitable and inclusive police organizations. Finally, this study explores areas such as training, recruitment, and warrior/guardian debate where change should be considered.